Pengaruh Model Problem Based Learning Berbantuan Miniatur Kincir Air Pembangkit Listrik untuk Meningkatkan Keterampilan Berpikir Siswa Sekolah Dasar - Fahruddin, Muhammad; Widiyono, Aan (Indo-MathEdu Intellectuals Journal, 2023)
21st century education develops 4C competencies (Creative, Critical thinking, Communication, Collaboration), including learning in Social Natural Sciences (IPAS). International surveys show that Indonesia has a level of student scientific ability below the global average. This research aims to determine the effect of the Problem Based Learning (PBL) learning model with the support of miniature power plant waterwheel media on students' critical thinking skills. This research uses a one-group pretest-posttest design. The research sample consisted of 10 students. Data collection tools through description tests. The results of the research show that there is a significant increase in students' critical thinking abilities after implementing the PBL model using a miniature waterwheel for power generation. The PBL model provides students with a more in-depth, active learning experience and the miniature waterwheel media helps students understand science concepts very well. This research underlines the importance of innovative models in science education to improve students' critical thinking abilities.